MEDICAL RECORD INFORMATION SYSTEM DESIGN OF PHYSIOTHERAPY CLINIC - Rahmat Dinur; Yohanes Manurung (INFOKUM, 2021)
Karya Suci Physiotherapy Clinic is one of the clinics located in Pematangsiantar city and is engaged in physiotherapy services. In the current digital 4.0 era, where all business elements rely on technology. Karya Suci encountered problems in the service process for patient data and medical records, where the service process still uses a manual system or has been computerized but uses Microsoft Office Excel. Which allows for a data shortage. To provide better services, an information system is needed to assist the process of collecting patient data and medical records. The Karya Suci application is a website-based application using the PHP programming language and utilizing the MySQL database as a database server that aims to assist the process of providing patient medical record data.